Characteristics of sweating responses and peripheral sweat gland function during passive heating in sprinters - Amano, T.; Koga, S.; Inoue, Y.; Nishiyasu, T.; Kondo, N. (European Journal of Applied Physiology, 2013)
The purpose of this study was to compare sweating function in sprinters who have trained for several years with untrained subjects and trained endurance runners. Two separate experiments were conducted. Nine sprinters, eight untrained men, and nine distance runners ( Vo2max 50.9 ± 1.4, 38.2 ± 1.8, and 59.1 ± 1.2 mL/kg/min, respectively; P < 0.05) were passively heated for 50 min (Experiment 1), and ten sprinters, 11 untrained men and nine distance runners (similar Vo2max levels compared with Experiment 1 in each group) had their sweat gland capacity assessed based on acetylcholine-induced sweating rate (SR) (Experiment 2). The slope of the mean non-glabrous SR plotted against change in mean body temperature during passive heating did not differ significantly between sprinters and untrained men (1.21 ± 0.10 and 0.97 ± 0.12 mg/cm^2/min/°C, respectively); in contrast, compared with untrained men, distance runners exhibited a significantly greater slope (1.42 ± 0.11 mg/cm^2/min/°C, P < 0.05). The mean body temperature threshold for SR was not significantly different among the groups. Acetylcholine-induced SR did not differ significantly between sprinters and untrained men, whereas distance runners showed a significantly higher induced SR compared with untrained men. The sweating function was not improved in sprinters who have trained 2-3 h/day, 5 days/week, for at least 3 years compared with untrained men, although the Vo2max was markedly greater in sprinters. Thus, there is a case that daily training was not sufficient to improve sweating function in sprinters relative to those in distance runners.